Estratégias de controle de ordem fracionária aplicadas ao amortecimento de oscilações eletromecânicas em sistemas elétricos de potência - AYRES JÚNIOR, Florindo Antonio de Carvalho (Universidade Federal do Pará, 2014)
In this work, a new project methodology was proposed to tune power systems stabilizers (PSS) based on fractional order systems theory (FOPSS). The strategy is based in a generalization of Lead-Lag compensators type project to fractional order transfer function domain. A new project variable, which defines the controller fractional order, is tuned to obtain a good compromise between the damping fulfillment of dominant electromechanical mode and the FOPSS amplified robustness. FOPSS performance was experimental evaluated, in a small-scalled system, located at Power Systems Laboratory of Federal University of Para. This test plant present a typical structure of synchronous generator connected to infinite bus and exhibits a decreased damping electromechanical dominant mode, whose around 1,2 Hz natural frequency value. So FOPSS was designed to improve relative damp of mode target, for all admissible operation range. For practical intent , first experimental tests was made to identify a plant nominal model in the form of a pulse transfer function, used in FOPSS project. This obtained model was validated and then used both to FOPSS project and conventional PSS (applied to performance comparison). The damp control rules of FOPSS were calculated, and then converted to difference equations, and subsequently, embedded in digital systems based on DSPIC microcontrollers. A couple of impulse test were made under different operational conditions. Respective dynamical responses data of plant output signals (active power deviation) and control effort were saved to analysis purposes. The experimental results showed that FOPSS presented a greater robustness and a similar performance compared to dynamical performance of conventional PSS, for all investigated operation range.